AN EMPIRICAL STUDY OF THE PREPAREDNESS OF YOUNG MEN AND WOMEN FOR A STABLE FAMILY LIFE (Eureka Journal of Education & Learning Technologies, 2026)
This article emphasizes that preparing young people for family life is one of the most pressing issues. While preparing for family life may seem to be a purely personal matter, unrelated to others, this perspective highlights the factors that protect the development of our nation, the morals of our people, our future, and our lineage from harm.
Keywords: Motives for starting a family, responsibility, maturity, spiritual knowledge, health, family life.